Qatar Foundation Annual Research Forum Volume 2013 Issue 1 2013
DOI: 10.5339/qfarf.2013.biosp-03
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of Muscle strength and short-term endurance in the different periods of type 2 diabetes

Abstract: Background: Patients with type 2 diabetes (T2DM) are subjected to reduction in the quality and oxidative capacity of muscles. The effect of duration of diabetes on the muscle endurance response is not clear and strength as well. Objective: The aim of this study was the assessment of strength and endurance of knee extensor and flexor in the patients with T2DM < 10 and T2DM > 10 years in comparison with age, sex, BMI, ABI and PAI-matched health control subjects. Methods: Isometric maximal peak torque (MPT) of kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 28 publications
2
5
2
Order By: Relevance
“…These data appears in contrast with those by Andersen et al , who recorded greater muscular endurance during isokinetic contractions of the knee and ankle extensors in insulin‐dependent diabetic patients than in non‐diabetic control subjects . Likewise, another, very recent, study reported greater isokinetic muscular endurance of the knee flexor muscles in patients suffering from diabetes for more than 10 years . However, the same muscle group under static conditions was found less resistant to fatigue.…”
Section: Muscle Dysfunction In T2dmcontrasting
confidence: 78%
See 2 more Smart Citations
“…These data appears in contrast with those by Andersen et al , who recorded greater muscular endurance during isokinetic contractions of the knee and ankle extensors in insulin‐dependent diabetic patients than in non‐diabetic control subjects . Likewise, another, very recent, study reported greater isokinetic muscular endurance of the knee flexor muscles in patients suffering from diabetes for more than 10 years . However, the same muscle group under static conditions was found less resistant to fatigue.…”
Section: Muscle Dysfunction In T2dmcontrasting
confidence: 78%
“…Clinical and experimental studies have demonstrated that T2DM is associated with a reduction in muscle strength (Table ). This impairment was shown to occur both in the upper and lower limbs , although the detrimental effect of diabetes differs between the upper and lower appendicular musculature, as reported also for muscle metabolism . Similar results have been reported in subjects with impaired glucose tolerance (IGT) and in newly diagnosed T2DM, suggesting that the defect of muscle strength affects diabetic patients since the early stages of the disease .…”
Section: Muscle Dysfunction In T2dmsupporting
confidence: 75%
See 1 more Smart Citation
“…With respect to decreased muscle strength in individuals with DM2, our results confirmed the findings of previous studies showing that individuals with diabetes have lower skeletal muscle strength than those without diabetes ( 28 , 29 ). The mechanism of muscle strength decline in DM2 subjects is not well defined.…”
Section: Discussionsupporting
confidence: 90%
“…Although, most in vivo studies have analyzed muscle performance under isokinetic conditions (both active (Hatef, Bahrpeyma, & Tehrani, 2014) and passive (Hajrasouliha, Tavakoli, Esteki, & Nafisi, 2005)), a simple, widely used and objective tool in a clinic for measuring muscle strength is hand-held dynamometer (Abizanda et al, 2012). Hand-held dynamometers have been shown to be reliable for testing a number of muscle groups including those of the ankle (Burns, Redmond, Ouvrier, & Crosbie, 2005;Wang, Olson, & Protas, 2002), but this device does not give any information about the individual muscle forces distribution.…”
Section: Introductionmentioning
confidence: 99%